EMPOWERING YOUTH GENERATION TO BE SUSTAINABLE IN INTERNATIONAL COMMUNITY - Hamidi, Ichsan; Delovarova, Leila F.; Suhel, Suhel; Sukanto, Sukanto; Atiyatna, Dirta Pratama; Imelda, Imelda; Habibi, Muhammad Ammar (Universitas Islam Malang, 2025)
This study highlights the urgent need to empower the youth generation to actively engage in the international community in addressing sustainability challenges. Issues such as climate change, social inequality, and food security require innovative solutions driven by young people. This community service initiative was designed to enhance youth participation through education, collaboration, and digital engagement. The program was conducted virtually via Zoom and involved participants from Sriwijaya University, Indonesia; Al-Farabi Kazakh National University, Kazakhstan; and ENS Lyon, France. The primary objective of this initiative was to equip youth with essential skills, knowledge, and attitudes necessary for contributing to sustainable development. The methodology employed included online workshops, interactive discussions, and collaborative projects focusing on sustainability practices. During the implementation phase, participants engaged in knowledge-sharing sessions, case study analyses, and social media campaigns to promote awareness and collective action. The results indicated that youth empowerment through targeted training and cross-border collaboration significantly enhances their capacity to address global issues effectively. The program demonstrated the role of digital technology and international networking in fostering sustainable practices among young individuals. Future initiatives should expand to include more diverse participants and incorporate hands-on community projects to further strengthen youth contributions to global sustainability efforts.